The mediating effect of intention to use of technology on the Relationship between Drivers, Barriers, and Consequences and the Use of Mobile Technology in the Workplace by Millennials - Lee, Macy Louie C. (Animo Repository, 2022)
The research entitled “The Mediating Effect of Intention to Use of Technology on the Relationship between Drivers, Barriers, and Consequences and the Use of Mobile Technology in the Workplace by Millennials” aims to determine if there is a mediating effect of the intention to use technology on the relationship between drivers, barriers and consequences and the use of mobile technology in the workplace by millennials. This study would provide relevant data, information and result that would determine the correlation and effects of the variables with one another and the mediating effect of intention to use. With that, this study would benefit entrepreneurs, millennials, academe, government and future researchers who want to conduct a similar study. In order to gather data for this research, the researchers have distributed a survey questionnaire to 210 millennial clerical workers who are employed in BGC, Makati and Ortigas. After data collection the researchers have use different statistical methods such as descriptive statistics, correlation, regression analysis and mediating analysis to answer their research problems. The researchers have found that the mediating effect of the intention of use on the relationship between drivers, barriers, and consequences and the use of mobile technology in the workplace by millennials is insignificant.